(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2022)
The article is devoted to the study of the pandemic as a legal prerequisite for the introduction of certain mechanisms for the observance of human rights in the conditions of emergency legal regimes and to the identification of certain features of the observance and guarantee of these rights. A number of domestic and foreign legal acts regulating the introduction of the state of emergency have been analyzed. The main purpose of introducing a state of emergency has been determined. The list of reasons for restricting human rights has been analyzed and attention has been drawn to international experience in preventing this negative phenomenon. It has been noted that each state operates with a sufficient amount of information in order to determine the level of public danger and thereby answer the question: if it is appropriate to limit human rights. State authorities within their competence are authorized to make decisions regarding the scope and nature of human rights restriction. The state, assessing a certain emergency situation, must do it correctly from the danger of the situation point of view and taking into account the relevant factors (whether there is public danger that threatens the life of the nation), if necessary, declare a state of emergency to combat it. A classification of legal regimes has been carried out, which include extraordinary and hybrid ones. It has been noted that the main difference between them lies in the constitutionalization of the first ones, which provide for a rather significant retreat of the state from ensuring a number of human and citizen rights and freedoms. Attention has been focused on the fact that, since a state of emergency can lead to the restriction of human rights, it is necessary to turn to the international experience of preventing this negative phenomenon. There are three main tools that human rights law uses to deal with emergencies: human rights exceptions; restriction of human rights; derogation of rights. Taking into account the peculiarities of the emergency situation, it is possible to limit the scope of human rights necessary to overcome the emergency situation, however, at the regulatory level, the list of constitutional rights and freedoms that may be limited and on what grounds should be clearly established.